Biotin-cGMP and -cAMP are able to permeate through the gap junctions of some amacrine cells in the mouse retina despite their large size - Yuan, Chunxu; Gerhards, Luca; Solov’yov, Ilia A.; Dedek, Karin (Frontiers in Ophthalmology, 2024)
Gap junctions transmit electrical signals in neurons and serve metabolic coupling and chemical communication. Gap junctions are made of intercellular channels with large pores, allowing ions and small molecules to permeate. In the mammalian retina, intercellular coupling fulfills many vital functions in visual signal processing but is also implicated in promoting cell death after insults, such as excitotoxicity or hypoxia. Conversely, some studies also suggested a role for retinal gap junctions in neuroprotection. Recently, gap junctions were also advocated as conduits for therapeutic drug delivery in neurodegenerative disorders. This requires the permeation of rather large molecules through retinal gap junctions. However, the permeability of retinal networks for molecules >0.6 kDa has not been tested systematically. Here, we used the cut-loading method and probed gap junctional networks in the mouse retina for their permeability to cGMP and cAMP coupled to Biotin, using the well-characterized tracer Neurobiotin as control. Biotin-cGMP and -cAMP have a molecular weight of >0.8 kDa. We show that they cannot pass the gap junctions of horizontal cells but can permeate through the gap junctions of specific amacrine cells in the inner retina. These amacrine cells do not comprise AII amacrine cells and nitric oxide-releasing amacrine cells but some unknown type. In summary, we show that some retinal gap junctions are large enough to let molecules >0.8 kDa pass, This is a provisional file, not the final typeset article making the intercellular delivery of therapeutic agentsalready successfully exploited, for example, in canceralso feasible in neurodegenerative diseases.